Simulation Model of Wind Turbine Power Control System with Fuzzy Regulation by Mamdani and Larsen Algorithms - Aziz, Ghada Adel (Al-Khwarizmi Engineering Journal, 2017)
Abstract The aim of this work is to create a power control system for wind turbines based on fuzzy logic. Three power control loop was considered including: changing the pitch angle of the blade, changing the length of the blade and turning the nacelle. The stochastic law was given for changes and instant inaccurate assessment of wind conditions changes. Two different algorithms were used for fuzzy inference in the control loop, the Mamdani and Larsen algorithms. These two different algorithms are materialized and developed in this study in Matlab-Fuzzy logic toolbox which has been practically implemented using necessary intelligent control system in electrical engineering and renewable energy concepts. A comparison was done to access the functionality of the developed power control system of fuzzy logic and classical control system with PID – control. It can be concluded that the power control system of fuzzy logic allows to accurately maintain production under the control target function for each work area. When switching operation of wind turbines, it has the distinction that from 13.5 m/s to another wind velocity value, there is no overshoot and a typical of classical control systems, and when the wind velocity V is less than13.5 m / s, the pitch angle of the blades should be slightly greater than zero, and if it has increased by 5 °, then blade length should be minimal as possible. Simulation program proved the possibility of effective power regulation for the large wind turbines controller fuzzy type on the basis of knowledge production "if - then" rules, which were shown to be effective on these wind turbines control. Keywords: Mamdani and Larsen algorithms fuzzy inference, Matlab Fuzzy Logic ,Fuzzy-PID controllers, Wind turbine.